PERAN SEKOLAH DALAM MENUMBUHKAN KESADARAN POLITIK SISWA SMP ASWAJA SYAMSUL FALAH - Putri, An Umillah Maziidah; Tahir, M.; Hanafi, Muh. Irfan; Zikro, Muhammad; Mustari, Muh. (Program Studi PGSD, FKIP, Universitas Mataram, 2025)
This research aims to determine the role of schools in raising students' political awareness at Aswaja Syamsul Falah Islamic Middle School and the obstacles faced by schools in raising students' political awareness at Aswaja Syamsul Falah Islamic Middle School. This research is a descriptive type qualitative research with purposive sampling technique. The informants in this research were 11 people consisting of the principal, deputy principal as well as a citizenship education teacher, OSIS supervisor, OSIS chairman, OSIS deputy chairman and 3 students of class VIII and 3 IX of Aswaja Syamsul Falah Islamic Middle School. The data collection techniques used were observation, interviews and documentation. The data obtained was analyzed using qualitative descriptive analysis through three stages, namely: data reduction, data presentation, and drawing conclusions. Next, the data validation technique uses a member check. The results of the research show that: 1) The role of the school in fostering students' political awareness at Aswaja Syamsul Falah Islamic Middle School is: a) the school as a forum for fostering student political participation through the election of the OSIS chairman, b) the school as a forum for forming a cadre of leaders through Basic Training Leadership (LDK), c) schools as a forum for providing political knowledge to students through Citizenship Education (PKn) learning. 2) The obstacles faced by schools in raising students' political awareness at Aswaja Syamsul Falah Islamic Middle School are the students themselves, namely the attitude of students who are: a) lazy, b) consider the activities of selecting the OSIS and LDK chairman to be useless for them and instead take up time. they are, c) students' lack of interest in Civics subject matter, and d) students' lack of curiosity